(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The growing use of mobile phones in academic environments has prompted serious concerns about their ability to distract students and compromise the integrity of exams. This study evaluates the effectiveness of an Active Mobile Phone Detection System (AMPDS) that has been implemented in an academic environment. The overall objective of the research is to determine the ability of the device to sense active mobile phones at a distance of 4 meters and its suitability in preserving discipline and reducing distraction. Other objectives of the research include testing device’s sensitivity under real-world conditions and determining its impacts on schools. The methodology employed involved the modeling and installation of the detection system in a controlled environment, where it was evaluated under diverse scenarios, such as mobile phone models, network setups, and human behavioral patterns. Some of the key parameters that were measured consisted of the detection rate, false alarm incidents, and levels of signal interference. The findings indicated that the AMPDS could identify active mobile phones with high accuracy, albeit with some interference from environmental circumstances. The finding suggests the possibility of having such a system implemented for mobile phone regulation in schools, particularly inside classrooms and exam halls. Moreover, the study contributes to the body of knowledge by providing empirical findings on mobile phone detection technologies in academic settings. Its usefulness could further be extended to potential application in schools, policy-making on mobile phone control, and potential future improvements in detection precision and range optimization.